ISOLATION AND IDENTIFICATION OF DIESEL DEGRADING MICROORGANISM FROM BARDDHAMAN LOCO SHED POND, BURDWAN, WEST BENGAL, INDIA - SMARANYA HAQUE, SUBINOY MONDAL,; APURBA R GHOSH, (The Bioscan, 2012)
Diesel fuel is considered as a common environmental pollutant comprised of a large number of both aromatic and aliphatic hydrocarbons. The present study was carried out to isolate hydrocarbon (diesel) degrading bacteria collected from the diesel fed pond known as Barddhaman Loco Shed Pond. The samples were analyzed microbiologically using standard microbiological techniques. These organisms were further studied to determine their biodegrading activities on hydrocarbons (diesel) as the sole carbon source using enrichment medium. Phenotype and phylogeny analysis of this strain was characterized and identified as diesel degrading bacteria, based on gram staining, 16S rRNA gene sequence analysis. These results indicate that this new strain was Pseudomonas sp. and showed 99% similarities with Pseudomonas mendocina and Pseudomonas pseudoalcaligenes with 99 % 16S rRNA gene sequence similarity.